Biochemical and Molecular Dynamics Study of a Novel GH 43 α-l-Arabinofuranosidase/β-Xylosidase From Caldicellulosiruptor saccharolyticus DSM8903 - Saleh, Md. Abu; Mahmud, Shafi; Albogami, Sarah; El-Shehawi, Ahmed M; Paul, Gobindo Kumar; Islam, Shirmin; Dutta, Amit Kumar; Uddin, Md. Salah; Zaman, Shahriar (Frontiers in Bioengineering and Biotechnology, 2022)
The complete hydrolysis of xylan can be facilitated by the coordinated action of xylanase and other de-branching enzymes. Here, a GH43 α-L-arabinofuranosidase/β-xylosidase (de-branching enzyme) from Caldicellulosiruptor saccharolyticus was cloned, sequenced, and biochemically investigated. The interaction of the enzyme with various substrates was also studied. With a half-life of 120 hours at 70 °C, the produced protein performed maximum activity at pH 6.0 and 70 °C. The enzyme demonstrated a higher activity (271.062 ± 4.83 U/mg) against para nitrophenol (pNP) α-L-arabinofuranosides. With xylanase (XynA), the enzyme had a higher degree of synergy (2.30) in a molar ratio of 10:10 (nM). The interaction of the enzyme with three substrates, pNP α-L-arabinofuranosides, pNP β-D-xylopyranosides, and sugarbeet arabinan, was investigated using protein modeling, molecular docking, and molecular dynamics (MD) simulation. During the simulation time, the Root Mean Square Deviation (RMSD) of the enzyme was below 2.5 Å demonstrating structural stability. Six, five, and seven binding interacting residues were confirmed against pNP α-L-arabinofuranosides, pNP β-D-xylopyranosides, and arabinan, respectively, in molecular docking experiments. This biochemical and in silico study gives a new window for understanding the GH43 family’s structural stability and substrate recognition, potentially leading to biological insights and rational enzyme engineering for a new generation of enzymes that perform better and have greater biorefinery utilization.